100 Ideas That Changed the World. - Osman, Jheni (BBC Books, 2011)
Every once in a while, an idea comes along that makes the entire world sit up and take notice.
Include Illustration and Index
Keywords: Science and civilization -- Technological innovations -- Technology--Social aspects